PROSPECTS FOR PRESERVING ETHNIC IDENTITY AND LANGUAGE IN A POLYMENTAL ENVIRONMENT (using the example of cross-border Dagestan languages) - Ataev, Boris Mahacevic; Ibragimova, Mariza Oglanovna; Magomedhanov, Magomedhan Magomedovic (History, Archeology and Ethnography of the Caucasus, 2024)
The article is devoted to the problems of preserving ethnic identity and language in a polymental environment. The object of the study is the speakers of the Avar, Lezgin, Rutul, Tsakhur, Bezhta and Gunzib languages in the focus of their cross-border status, which affects ethnic identity. The difference in the social, ethnic, mental environment of divided peoples causes dissonant phenomena in the formation of ethnic identity among speakers of cross-border languages. From the perspective of sociolinguistic methods, the prospects for preserving the ethnic identity of speakers of cross-border Dagestan languages are described. The phenomena of ethnic identity of speakers of cross-border Dagestan languages are characterized in the context of adaptation to the conditions of states with differences in culture, language of communication, mentality, religion and other areas. Based on an analysis of the specific linguistic portrait of speakers of trans-border Dagestan languages and a description of cultural associations characteristic of their modern sociolinguistic status as divided peoples, trends towards hybridization of cultures, gradual unification of languages of universal human values are traced, with certain adjustments taking into account the religious views of residents of bordering states. The theoretical significance of the article lies in the scientific forecasting of the ways of linguistic and cultural adaptation of speakers of cross-border Dagestan languages, based on an analysis of the current situation, reflecting the conditions for preserving the languages and ethnic identity of divided peoples. The methods and techniques used can be applied to the analysis of other cross-border languages localized in multicultural regions.
Keywords: cross-border languages; ethnic identity; multilingual regions; polymental environment; linguistic and cultural adaptation